Transfer Pricing in Mining with a Focus on Africa : A Reference Guide for Practitioners - Guj, Pietro; Martin, Stephanie; Maybee, Bryan; Cawood, Frederick; Bocoum, Boubacar; Gosai, Nishana; Huibregtse, Steef (World Bank, Washington, DC, 2017)
This book presents the results of a study on transfer pricing (TP) with specific focus on mining in Africa commissioned in early 2014 by the World Bank Group (WBG) in partnership with the International Mining for Development Centre (IM4DC). The Source Book opens with the Introductory chapter identifying the need for the study and the way it was conducted. This is followed by the main body of the book that includes three parts. Part A (The mining industry and transfer pricing) identifies what are the most common transfer pricing issues in mining in general and where they are likely to occur along the mining value chain. Part B (The mining industry in Africa and transfer pricing) considers the same issues specifically in the context of the main commodities currently mined in Africa. This part and its related appendices provide a comprehensive inventory of current mining operations in Africa and information about the revenue and cost structure of typical operations to help establish a methodology for the assessment and prioritization of transfer pricing risks, supported by practical examples and case studies. Part C (Institutional and administrative capacity) then relates to the question of how to prioritize and address the issues covered in Parts A and B and discusses the resourcing, skills and organizational structures necessary to ensure that the arm’s length principle is successfully abided to. The book closes with a Discussion and Conclusions chapter which summarizes the results of the study and the main strategies identified as appropriate to improve industry’s compliance with sound TP principles and the capacity of tax authorities to carry out an adequate level of effective TP auditing, thus minimizing revenue leakages. Relevant examples and case studies are provided throughout the text in the form of Boxes identifiable by a distinctive greenish-grey colored background.